The effect of core stability training on the balance ability of young male basketball players - Gong, Jian; Gao, Huiyan; Sui, Jinghao; Qi, Fei (Frontiers in Physiology, 2024)
Introduction: This study aimed to investigate the impact of a 10-week Core Stability Training (CST) compared to Traditional Strength Training (TST) on the balance abilities of adolescent male basketball players. Methods: Subjects (age: 15.70 ± 0.75, height: 178.4 ± 8.31, weight: 66.55 ± 8.34) were randomly assigned to either the Core Stability Training group or the Traditional Strength Training group. Three selected balance assessment indicators included the Single-leg Standing with Eyes Closed Test, Star Excursion Balance Test, and Core Four-Direction Endurance Test. Results: 1) The scores were significantly different in both groups before and after the Single-leg Standing with Eyes Closed Test; (p < 0.01, d = 1.692, d = 1.837); 2) In the Star Excursion Balance Test, the scores of the experimental group showed significant difference (p < 0.05) or highly significant difference (p < 0.01) with an average effect size of (d = 1.727) when the left or right foot supported in the other directions before and after the training. However, there was no significant difference in scores in the c direction when the left foot supported (p > 0.05, d = 0.954); 3) In the Core Four-Direction Endurance Test, there were no significant differences in scores for the control group before and after training (p > 0.05, d = 0.567), while the experimental group showed significant differences in scores before and after training (p < 0.05, d = 1.889). Discussion: Both CST and TST were effective in enhancing the balance abilities of adolescent basketball players. CST, in particular, demonstrated improvements in dynamic balance and agility across multiple planes. Basketball coaches are encouraged to consider incorporating CST training programs into their overall training plans for optimal balance enhancement.